The relationship between MMP-9 promoterpolymorphism and IVF outcome - Shabanipour, S; Mashayekhi, F; Bahadori, M H; Soruri, Z Z (Cellular and Molecular Biology, 2015)
Angiogenesis, invasion and decidualization play an important role in implantation and embryo development. Matrix metalloproteinases (MMPs) are crucial for the degradation/remodeling of the extracellular matrix, and are involved in spiral artery formation and invasion of endometrium during implantation. A functional single-nucleotide polymorphism (SNP) in the MMP9 promoter, -1562C/T, is known to influence gene expression in allele-specific manner. The present study evaluated the association between maternal genotype of SNP -1562C/T of MMP9 and in vitro fertilization and embryo transfer (IVF-ET) outcome in infertile women. This case-control study was comprised of infertile patients (n= 123) and women having one healthy child as controls (n= 147). Genotyping for SNP-1562C/T was performed by PCR/RFLP. Allele and genotype distribution did not differ significantly between patients and controls (P>0.05). The MMP9 genotype frequencies amongst the 123 cases were C/C=73.17%, C/T=24.40% and T/T=2.43%; the C and T allele frequencies were 85.36% and 14.63%, respectively. The MMP9 genotype frequencies amongst the 147 controls were C/C=73.46%, C/T=20.40% and T/T=6.12%; the C and T allele frequencies were 83.67% and 16.32%, respectively. In conclusion, the results of this study indicate that SNP -1562C/T of MMP9 may not be associated with IVF-ET outcome in this population.